STRATEGI GALLERY WALK BERBASIS SOCIO-SCIENTIFIC ISSUES UNTUK MENINGKATKAN LITERASI LINGKUNGAN DAN SIKAP PEDULI LINGKUNGAN - Hafiz Fadhal Muhammad; Hasan Subekti (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aimed to describe learning using Gallery Walk strategy based on Socio-Scientific Issues (SSI) for students’ environmental care attitude and literacy in environmental pollution topic. The study used pre-experimental with one group pretest-posttest. The subjects of this study was 15 students of VII grade in middle school. The data were collected by observation, test, and survey techniques with the instrument were used observation sheets of learning implementation, student activities, environmental literacy tests, and environmental care attitude questionnaires. The environmental literacy test and environmental care attitude questionnaires were used for analyzed the students competency before (pretest) and after (posttest) the learning. The results showed that learning using Gallery Walk strategy based on SSI affects the students environmental literacy and environmental care attitude. The results of the N-Gain showed that students environmental literacy and environmental care attitude increased in the medium category. This improvement also supported by well-implemented Gallery Walk strategy based on SSI’s learning. The results of this study can be used as a reference for implementing learning using Gallery Walk strategy based on SSI on other topics, so that it can be implemented optimally and achieve the learning goals